Determination of Chronic Kidney Disease Severity in Patients with Diabetic Nephropathy: A KDIGO-Based Cross-Sectional Study - Begum, Mahammad Salar; Jahnavi, Yaramalla; Nemitha, Markapudi; Ahmed, Alamin; Azharuddin, Mohd; Chinnaeswaraiah, Maram (Asian Journal of Biological and Life Sciences, 2026)
Background: Diabetes mellitus is a major global health problem and one of the leading causes of Chronic Kidney Disease (CKD). Diabetic nephropathy is a serious microvascular complication characterized by persistent albuminuria, progressive decline in Glomerular Filtration Rate (GFR), and increased risk of end-stage renal disease. Early identification of disease severity using Kidney Disease: Improving Global Outcomes (KDIGO) classification is important for timely intervention and prevention of disease progression. Aim: To evaluate the impact of diabetes mellitus on the progression of diabetic nephropathy using KDIGO classification. Materials and Methods: Conducting a cross-sectional observational study CKD severity was assessed using KDIGO classification based on estimated Glomerular Filtration Rate (eGFR) and albuminuria categories. Statistical analysis was performed using the χ2 test. Results: Among 200 patients, Severe CKD (G4-G5) was observed in 87.5% of patients and severe Albuminuria (A3) in 89%. According to KDIGO risk classification, 95.5% of patients were categorized as very high risk. Significant associations were found between CKD severity and HbA1C levels and blood pressure (p<0.001). Conclusion: The study demonstrates a high burden of advanced CKD among diabetic nephropathy patients. Poor glycemic control and uncontrolled hypertension were significantly associated with CKD progression, highlighting the importance of early screening and effective management of diabetes and blood pressure.
Keywords: Diabetes mellitus; Diabetic nephropathy; Chronic kidney disease; KDIGO classification; Glycemic control; Hypertension